How to catch a snowman ebook - Wallace, Adam (How to Catch., 2020)
A USA Today Bestseller! From the New York Times and USA Today bestselling How to Catch series comes a new winter adventure! Our heroes' entry for the snowman contest has magically come to life—and ran away! Can YOU help catch it? Get ready for snow much fun as you travel through a winter wonderland with running, skating, and bouncing through trap after trap to catch the snowman and claim the winning prize. Will the snowman teach our heroes a lesson they'll never forget? Who snows! This delightful picture book for ages 4-10 is filled with silly rhymes, fun art, and STEAM connections perfect for families and educators to enjoy this winter or as a holiday stocking stuffer. I don't thumpity-thump or give warm hugs—that's for my snowman friends to do. Clever kids will try to trap me, but who will catch me...YOU? Also in the How to Catch Series: How to Catch a Yeti How to Catch a Mermaid How to Catch a Dinosaur How to Catch an Elf How to Catch a Monster and more!